Методологічні підходи до фінансового аналізу та оцінки ефективності бюджетних видатків - Качула, Світлана Валентинівна; Kachula, Svitlana (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
Стаття присвячена дослідженню методологічних підходів проведення фінансового аналізу та оцінки ефективності бюджетних видатків як інструментів підвищення результативності управління публічними фінансами. Розглянуто сутність і класифікацію бюджетних видатків, визначено їх роль у забезпеченні соціально-економічного розвитку. Проаналізовано традиційні та сучасні методи фінансового аналізу, зокрема динамічний, структурний, факторний, а також методи «вартість–результат», «вартість–ефективність» і «вартість–корисність». Окрему увагу приділено застосуванню програмно-цільового підходу, системи ключових показників ефективності (KPI) та аудиту ефективності у державному секторі. Узагальнено міжнародний досвід оцінювання бюджетних видатків та можливості його адаптації в Україні. Запропоновано практичні рекомендації щодо вдосконалення методичної бази аналізу, інтеграції цифрових інструментів та підвищення прозорості бюджетного процесу для забезпечення ефективного використання державних ресурсів. This article provides a comprehensive examination of the methodological approaches to financial analysis and the evaluation of the efficiency of budgetary expenditures, which are essential for improving the effectiveness and transparency of public financial management. It begins with an analysis of the concept and classification of budget expenditures, emphasizing their critical role in ensuring sustainable socio-economic development. The study explores traditional financial analysis methods, including trend analysis, structural analysis, and factor analysis, alongside contemporary techniques such as cost-benefit analysis (CBA), cost-effectiveness analysis (CEA), and cost-utility analysis (CUA). Particular attention is devoted to the application of the program-targeted budgeting approach, the establishment and monitoring of key performance indicators (KPIs), and the role of performance auditing in enhancing accountability within the public sector. Furthermore, the article synthesizes international best practices and frameworks for assessing budget expenditure efficiency, highlighting successful cases from OECD and EU countries. It discusses the challenges and opportunities related to adapting these approaches within the Ukrainian fiscal context, considering institutional and regulatory particularities. The integration of digital analytical tools and big data technologies is also addressed as a means to increase the accuracy and timeliness of financial assessments. The research concludes with practical recommendations aimed at refining the methodological toolkit for evaluating budget expenditures, promoting evidence-based decision-making, and fostering greater fiscal discipline and transparency. These improvements are vital for optimizing public resource allocation, enhancing the effectiveness of government programs, and ultimately contributing to socio-economic progress.
Methodological approaches to financial analysis and the assessment of budget expenditure efficiency
Keywords: фінансовий аналіз; financial analysis; бюджетні видатки; budget expenditures; ефективність; efficiency; бюджетний контроль; budget control; програмно-цільовий підхід; program-target approach; ключові показники ефективності (KPI); key performance indicators (KPI); публічні фінанси; public finances